An analytic hierarchy process model for selecting adsorbent for heavy metal ion removal from wastewater - Shereen Ababneh; Omar Al-Araidah; Mohammed Almomani (Water SA, 2020)
This paper provides an analytic hierarchy process (AHP) model for the selection of an adsorbent to adhere with multiple types of metal ions from wastewater. Experimental literature is surveyed to estimate the entries for comparison matrices. The model allows the user to combine the degree of importance of the adsorption of each ion type to the degree of importance of both technical and non-technical criteria. A case study is provided to select among three adsorbents and three types of ions. Results illustrate the usability of the model in handling experimental problems; chitosan is selected for its high technical qualities, that sludge is preferred for its availability and low cost, and that pH-level and adsorbent-dosage are the most influential sub-criteria to control to enhance adsorption efficiency. Moreover, sensitivity analysis shows that the decision is impacted by the relative importance of technical criteria and by the degree of importance of ions.